Applications of health related quality of life (HRQoL) as an intervention impact assessment in the management of hypertension: a systematic review - Akeem, Bolarinwa Oladimeji; Aniema, Essiet Inimfon; Juni, Muhamad Hanafiah; Mohd Zulkefli, Nor Afiah; Md Said, Salmiah; Akande, Tanimola Makanjuola (American Association for Science and Technology, 2015)
Introduction: Persons living with hypertension wrestle with the physical, psychological, and social demands of their illness without adequate help or support from medical care. This has buttressed the need to research into the perceptions of patients in the context of their subjective feelings towards their wellbeing. This is termed “health related quality oflife (HRQoL)”. One of the most important goals of all health interventions is to improve the quality of life of persons affected by disease and many researchers had advocated for the need to see health outcome beyond clinical and laboratory parameter alone. Therefore need to study and assess HRQoL as well. This study however set out to review available intervention studies in the scientific literature from 1980 till date (that met the set eligible criteria) and those which employed quality of life as a primary outcome measurement.